Khadijahâ€™s feminism and polygamy in cinema: A re-examination of gender equality in Islam and Indonesian film - Ririe Rengganis; Putri Retnosari; M. Erwan Saing (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Research on polygamy in Indonesian cinema has largely been dominated by Western feminist perspectives and moral-sociological approaches, often overlooking the progressive theological dimensions embedded within Islamic teachings. Yet Islam offers the exemplary figure of Khadijah Ra. bint Khuwaylid, whose life embodies ethical leadership, economic autonomy, and gender justice. This study formulates the concept of â€œKhadijah Feminismâ€ as a theological-ethical framework and examines the representation of women and polygamy in four Indonesian films: Berbagi Suami (2006), Surga yang Tak Dirindukan (2015), Madu Murni (2023), and 1 Imam 2 Makmum (2025). Employing Faircloughâ€™s Critical Discourse Analysis, the research integrates textual-narrative analysis, cinematographic interpretation, and Islamic feminist hermeneutics through the ethical lens of Khadijah. The findings demonstrate that most films continue to reproduce patriarchal religious discourses by portraying womenâ€™s patience and obedience as the primary indicators of piety while marginalizing Khadijahâ€™s model of agency, justice, and moral leadership. In contrast, Madu Murni and Berbagi Suami present female protagonists who challenge patriarchal norms through economic independence, ethical reasoning, and resistance to injustice. Furthermore, polygamy is predominantly represented as a male privilege rather than as a morally accountable institution constrained by the Qur'anic principles of justice articulated in An-Nisa (4):3 and (4):129. This study contributes to Islamic feminist scholarship by introducing â€œKhadijah Feminismâ€ as an alternative analytical framework that integrates faith, gender equality, and spiritual agency, while recommending more theologically grounded and ethically responsible representations of Muslim women in contemporary Indonesian cinema.